Analisis Pelaksanaan Program Keluarga Harapan (PKH) dalam Meningkatkan Kesejahteraan Keluarga Penerima Manfaat di Desa Massewae Kecamatan Duampanua Kabupaten Pinrang (Perspektif Ekonomi Islam) - Nurfadilah; Desy Arum Sunarta; Rasyidah Bulqis (STAI DDI Pinrang, 2025)
Poverty is a major challenge in development, including in Massewae Village, Duampanua District, Pinrang Regency. The Family Hope Program (PKH) is here as an effort to overcome this problem by providing financial assistance to underprivileged families. However, the distribution of assistance still experiences obstacles that require attention so that it is right on target. This study aims to analyze the effectiveness of PKH implementation in Massewae Village and its compliance with Islamic economic principles. Qualitative descriptive methods are used with observation, interview, and documentation techniques. The research subjects include recipients, assistants, PKH leaders, and related parties in program implementation.The results of this study indicate that: 1) The implementation of PKH has a positive impact on improving welfare, especially in health, education, and social aspects. However, there are still negative impacts in the form of dependence on aid. 2) Based on the perspective of Islamic economics, PKH in Massewae Village has reflected the principles of monotheism and balance, but still faces challenges in terms of the principles of caliphate and distribution justice.